Differences in the electrical activity and the clinical performance of superficial neck flexors and extensors during the CCFT in women with migraine - Mendes , Luana Maria Ramos; Rodrigues, Amanda; Bragatto , Marcela Mendes; Florencio, Lidiane Lima; Dach , Fabíola; Fernández-de-las-Peñas, César; Bevilaqua-Grossi, Débora (Headache Medicine, 2022)
Introduction Musculoskeletal disorders in the cervical spine have been increasingly investigated and observed in patients with migraine. One of them is a poorer cervical muscle performance as assessed by the cranio-cervical flexion test (CCFT). In addition, patients with migraine have alterations in the recruitment of muscle motor units observed by surface electromyography during CCFT. Objective The aim was to verify if there are differences in the electrical activity and the clinical performance of superficial neck flexors and extensors during the CCFT in women with migraine considering the presence or absence of concomitant neck pain symptoms. Methods A total of 100 women were assessed: 25 with migraine without neck pain, 25 with migraine and neck pain, 25 with mechanical neck pain and 25 pain-free control. Clinical and demographic data were collected, The CCFT was performed in all groups. The test assessed the deep flexors muscle by a pressure unit biofeedback placed in the posterior region of the neck and initially inflated to 20 mmHg composed by 5 stages, with increase pressure by 2 mmHg at each stage, reaching 30 mmHg, keeping the pressure for 10 seconds without resorting to compensation. Electromyography data were collected with TrignoTM Wireless System wireless surface sensors. The sensors were firmly attached bilaterally on: sternocleidomastoid (SCM); splenius capitis, anterior scalene and upper trapezius. Electromyographic activity evaluated during the CCFT was normalized by the average the root mean square (RMS) calculated for the reference voluntary contraction and expressed as a percentage. Groups comparisons were performed with non-parametric tests adopting a level of significance of 0.05. To analyze the between-groups differences on the proportion of clinical targeted performance stages reached by each participant within the CCFT, the chi-square (X2) test was calculated, and the data were submitted to a post-hoc proportion test. (To see the complete abstract, please, check out the PDF).